Severe Consequences of the Development of Periodontal Disease in the Example of Employees Working in Light Industrial Plants - Nortaev A.B; Usmanov R.Dj; Ibragimova SH.A. (Zien Journals, 2023)
The article provides information about employees working in light industry production factories and periodontal disease, its development, spread, as well as its serious consequences.
Keywords: employee; periodontist; disease; male